Bibliometric Analysis of Development of Physics Learning Media Based on Educational Games: A Systematic Literature Review: Analisis Bibliometrik Pengembangan Media Pembelajaran Fisika Berbasis Game Edukasi: Tinjauan Pustaka Sistematis - Nurfaridah (Harati : Journal of Science Education, 2024)
Physics is an abstract subject that requires visualization, so learning media is needed so that students are able to understand the concepts being studied. One of the learning media that displays visualization using technology is educational games. This research aims to analyze the development of educational game learning media in physics learning with a bibliometric approach using VOSViewer software. The method used in this research is bibliometric analysis. There are 6 classification clusters via VOSViewer software. The research results showed that articles were used with the titles "educational games" and "learning media", and the keyword "physics learning" began to increase rapidly in 2018, 2019, 2020 and 2021. These articles were produced from various universities in Indonesia and use Indonesian. In this research, 4 clusters were obtained which discussed topics regarding the development of educational game learning media in physics learning. On the topic of developing learning media for educational games, quite a lot has been done, but on the topic of the effectiveness of using educational games in physics learning, research has rarely been carried out.